HTLV-1 HBZ PROTEIN DEREGULATES INTERACTIONS BETWEEN CELLULAR FACTORS AND THE KIX DOMAIN OF p300/CBP - Cook, Pamela R. (2011)
The complex retrovirus Human T-cell Leukemia Virus type I (HTLV-1) is the causative agent of adult T-cell leukemia (ATL). Deregulation of cellular transcription is thought to be an important step for T-cell transformation caused by viral infection. HTLV-1 basic leucine zipper factor (HBZ) is one of the viral proteins believed to be involved in this process as it deregulates the expression of numerous cellular genes. In the context of the provirus, HBZ represses HTLV-1 transcription, in part, by binding to the homologous cellular coactivators p300 and CBP. These coactivators play a central role in transcriptional regulation. In this study we determined that HBZ binds with high affinity to the KIX domain of p300/CBP. This domain contains two binding surfaces that are differentially targeted by multiple cellular factors. We show that two ϕXXϕϕ motifs in the activation domain of HBZ mediate binding to a single surface of the KIX domain, the mixed-lineage leukemia (MLL)-binding surface. Formation of this interaction inhibits binding of MLL to the KIX domain while enhancing the binding of the transcription factor, c-Myb to the opposite surface of KIX. Consequently, HBZ inhibits transcriptional activation mediated by MLL and enhances activation mediated by c-Myb. CREB, which binds the same surface of KIX as c-Myb, also exhibited an increase in activity through HBZ. These results indicate that HBZ is able to alter gene expression by competing with transcription factors for occupancy of one surface of KIX while enhancing the binding of factors to the other surface.